Rejuvenating immunity: “anti-aging drug today” eight years later - Blagosklonny, Mikhail V. (Oncotarget, 2015)
The 2014 year ended with celebration: Everolimus, a rapamycin analog, was shown to improve immunity in old humans, heralding ‘a turning point’ in research and new era in human quest for immortality. Yet, this turning point was predicted a decade ago. But what will cause human death, when aging will be abolished?